QUALITY OF LIFE AND TYPE 2 DIABETES BY EQ-5D-5L: INTEGRATIVE REVIEW - Barbosa Rocha, Nivia; de Araújo Pinheiro, Emanuel; Fernandes de Almeida Lima, Lucélia; Fernandes Bezerra Girão, Deysen Kerlla (Cadernos ESP, 2024)
Analyze the scientific publications on the EQ-5D-5L scale that assesses QoL in patients with type 2 Diabetes Mellitus. This is an integrative review built through the intersection of the following Health Sciences Descriptors (DeCS/MeSH): "Type 2 Diabetes Mellitus"; "Quality of life"; "Impact"; "Personal satisfaction" and their English equivalents "Type 2 Diabetes Mellitus", "Quality of life", "Impact" and "Personal satisfaction". The terms were combined using the Boolean operators "and" or "or". Data collection took place from September to October 2023. Manuscripts published between 2006 and 2023, which consisted of quantitative studies written exclusively in English, were meticulously examined. That analysis encompassed eight investigations that converged on the conclusion that patients diagnosed with DM2 have a compromised QoL. A notable aspect highlighted by the studies is the disparity between men and women affected by DM2, with women experiencing a particularly significant reduction in quality of life. That phenomenon was quantified using the EQ-5D-5L scale. Those results highlight the importance of differentiated and personalized approaches for both sexes in the management and support of patients with DM2. Exploring the different dimensions of quality of life in patients with DM2 goes beyond a mere challenge; represents a significant advance for the multidisciplinary team, emphasizing the importance of a collective approach. This expanded perspective enables a more comprehensive understanding of the needs and impacts on patients’ lives, encouraging more integrated and effective action by health professionals.